EXPLORING THE EFFECTIVENESS OF ERROR ANALYSIS IN IMPROVING GRAMMAR PROFICIENCY - Mukhlisin (Suluh Adiluhung Publisher (SAPub), 2025)
This study investigates the effectiveness of error analysis as a pedagogical approach to improving grammar proficiency among Islamic Education students at STAI Miftahul Ula, Nganjuk. Recognizing the persistent challenges students face in mastering grammatical accuracy, this research highlights the need for innovative teaching methods. A mixed-methods design was employed, integrating both quantitative and qualitative approaches. The sample consisted of 60 students selected through purposive sampling, divided into an experimental group using error analysis techniques and a control group employing conventional methods. Data were collected using grammar proficiency tests, reflective journals, and semi-structured interviews. Quantitative data were analyzed using paired t-tests, while qualitative data were thematically analyzed. The results demonstrated a statistically significant improvement in grammar proficiency for the experimental group compared to the control group (p < 0.05). Key qualitative themes included increased metalinguistic awareness, enhanced engagement, and positive attitudes toward learning grammar. The findings suggest that error analysis fosters a deeper understanding of grammatical rules by allowing students to identify and correct their mistakes. This study fills a gap in the literature by focusing on error analysis within the context of Islamic Education, where grammar is crucial for comprehending classical Arabic texts. Practical implications include integrating error analysis into language curricula and providing teacher training to implement this approach effectively. Future research should explore the long-term impact of error analysis on language retention and extend the study to diverse educational settings. This research not only contributes to the theoretical understanding of error analysis but also offers actionable insights for improving grammar instruction in higher education.